Health Care Professional’s Opinions on Culture and Rehabilitation Services for Youth Experiencing Early Psychosis - Hiba , Zafran (International Journal of Psychosocial Rehabilitation, 2015)
Background. Early intervention programs for youth experiencing early psychosis aim to facilitate access and community reintegration. Yet, the Mental Health Commission of Canada has identified stigma and discrimination in accessing and receiving mental health services as one of the primary obstacles to the community participation of persons with mental illness.Purpose. To explore the opinions of expert health care professionals on the service barriers to community integration for youth with psychosis, in order to inform the improvement of a rehabilitation program.Methods. Interview-based qualitative descriptive study (n=6) analyzed within the person-environment- occupation template.Findings. The primary barriers to community participation are described within sociocultural environments. Specifically, the lack of culturally informed practices within clinical and rehabilitation care significantly contribute to client access and involvement in rehabilitation programs. Implications. Cultural sensitivity and competency training for therapists can help to move policy into action for family-focused, values-based, early intervention rehabilitation practices.